Effect of trace elements in the toxicity of copper to Chlamydomonas reinhardtii. Issue 4 (10th March 2022) - Chen, Hui; Shen, Xin; Ying, Yiping; Li, Xiang; Chen, Lili; Shen, Chensi; Wen, Yuezhong
Abstract : The cell walls of microalgae have an impact on the toxic effects of Cu. The addition of Cu increased the accumulation of Fe Mn, and Zn by both cell types. Abstract : Copper sulfate (CuSO4 ) is widely used in the control of algal blooms. Cu can promote or inhibit algal growth, while also affecting trace element uptake, therefore, the response mechanisms of algae cells under Cu 2+ interference should be studied. In this study, wild-type Chlamydomonas reinhardtii ( C. reinhardtii ) and wall-less mutant C. reinhardtii were selected as the research objects. Except for the cell wall, these two algae were physiologically the same. While manipulating the concentration of Cu, the accumulation of Cu, Fe, Zn, and Mn by the two algal cell types was studied. The cell wall hindered the accumulation of Cu by cells and alleviated the toxicity of Cu to C. reinhardtii . The addition of Cu increased the accumulation of Fe by both cell types. In an environment with excess Cu, the total amount of Zn and Mn accumulated by cells also increased. On the one hand, this may be due to the synergistic and antagonistic effects of trace elements in the adsorption and uptake process, and on the other hand, it may be due to the changes in metal speciation in the culture medium. In addition, the difference in the total accumulation of various trace elements between wild-type and wall-less-type C. reinhardtii may be due to the structure and function differences between cell wall and cell membrane. At the same time, by measuring the changes in the levels of glutathione (GSH) in algal cells, the relevant mechanisms underlying the algae's uptake of trace elements by algae were further explored.